Functional effects of a prosthetic torsion adapter in trans-tibial amputees during unplanned spin and step turns - Heitzmann, Daniel; Alimusaj, Merkur; Block, Julia; Putz, Cornelia; Wolf, Sebastian Immanuel (Prosthetics and orthotics international, 2016)
Background:Shear stress at the stump in trans-tibial amputees induced by turning movements may be reduced with the use of torsion adapters in the prosthesis.Objective:Monitoring the motion and kinetic effects of a regular torsion adapter in comparison to a rigid placebo in unplanned spin and step turns.Study design:Single-blinded placebo-controlled cohort study.Methods:In total, 10 trans-tibial amputees underwent three-dimensional gait analysis in level walking and unplanned spin and step turns with a torsion adapter and with a rigid placebo.Results:Kinetic effects varied among participants. No statistically significant reduction of peak internal and peak external transverse plane moments was found for the torsion adapter in any walking condition. However, transverse plane rotation of the adapter was monitored in all participants.Conclusion:Motion between the socket and the residual limb may be reduced during turns due to transverse plane motion of the torsion adapter and shear stress on the residual limb may be reduced. However, there may be good and bad responders to torsion adapters due to differences in coupling between the residual limb and the socket.Clinical relevanceStrong coupling between stump and socket will help the user controlling his prosthesis. Shear stress at the stump may increase in stump?socket interface stiffness and may be the reason for residual limb problems. Torsion adapters therefore may be beneficial for comfort and stump condition in individual cases.